PELATIHAN PEMBELAJARAN PAUD YANG FUN DAN BERBUDAYA MELALUI METODE STEAM BERBAHAN LOOSE PART - I G. A.P. Arya Wulandari; Putu Sri Astuti; I Nyoman Suparsa (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
This workshop program has been successfully implemented. The indicators of success are shown by the activities, liveliness, and products produced by 25 PAUD teachers in the Tabanan Regency Education Office in the even semester of the 2021/2022 academic year. During the activity, the Kindergarten and PAUD teachers as workshop participants looked very enthusiastic about participating in the given workshop activities. This is shown by the many questions raised by kindergarten and PAUD teachers related to the topic of the workshop given. Some important questions raised by kindergarten and PAUD teachers were related to the relevance material workshop provided, namely regarding the STEAM method made from LOOSE PART, as an innovative learning model in learning. Apart from that, in practice during workshops the teacher is also asked to complete the product which will then be evaluated by the resource persons. In this activity, the resource person also conveyed several inputs related to the products that had been produced by each group.